PKM Optimalisasi Pengelolaan Limbah Plastik di Desa Gubug - Akbar, Shofif Sobaruddin; Ika Menarianti; Ernawati Saptaningrum (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2024)
Waste, especially plastic, is a serious problem in Indonesia. Consumer habits that use plastic products excessively cause an increase in plastic waste which is difficult to decompose and is dangerous for the environment. Waste Management Law: Law Number 18 of 2008 concerning Waste Management (UUPS) defines waste as the remains of human activities or natural processes in solid form. Waste management must be carried out systematically, comprehensively and continuously to prevent environmental pollution and health problems. Creativity in Using Plastic Waste: Converting plastic waste into handicrafts is an effective solution for reducing the amount of plastic waste and providing added value. This service stage is carried out by starting preparations, in this preparation the service team carries out site observations to see conditions in the field. Then prepare the material that will be given. The service team prepared materials according to the needs of Gubug Village. At this socialization and implementation stage, the service team provides outreach regarding the dangers of plastic waste and the management of plastic waste as well as how to market it. The fourth stage is monitoring, the service team determines whether the Gubug Village Community is able to make crafts from plastic waste.